PENGARUH HARGA DAN KUALITAS BIJI KOPI TERHADAP PENDAPATAN PETANI PADA DISTRIBUTOR JHODY DI KECAMATAN WARKUK RANAU SELATAN - Sally Maria Bramana; Evandry Deswana; Dwi Yuni Hartati (STIE DWI SAKTI BATURAJA, 2022)
This study discusses the Effect of Price and Quality of Coffee Beans on Farmers' Income at Jhody Distributors in Warkuk Ranay Selatan District. The method used in this research is descriptive method. The method used in this research is qualitative and quantitative analysis techniques. Based on the calculation of the correlation coefficient, the R value is 0.938, it can be interpreted that the correlation analysis of the relationship between price (X1) and the quality of coffee beans (X2) on the income variable (Y) is very strong. The result of the coefficient of determination or R Square is 0.880 or equal to 88%. This shows that income (Y) is influenced by 88% of the contribution of price (X1) and coffee bean quality (X2) while the remaining 12% is explained by other factors not explained in this study. Based on the results of partial and simultaneous hypothesis testing, it was found that there was an effect of the price and quality of coffee beans on farmers' income at Jhody Distributors in Warkuk Ranau Selatan District.